Assessment of Yield Parameters in M3-Generation of Chickpea (Cicer arietinum L.) Treated with Different Concentrations of EMS - Uddin MD Waseem; G. Vijay Kumar; K. Srinivas Naik (International Journal of Economic Plants)
The present study was conducted from February, 2023 to July, 2023 at Centre for Plant Molecular Biology, Osmania University, Hyderabad, Telangana (500007), India. Which involves two chickpea genotypes IC265291 (V1) and IC265298 (V2) which were obtained from NBPGR, New Delhi. The aim of the study is effect of different concentrations of EMS (Ethyl Methyl Sulfonate) on the yield parameters of chickpea plants in M3 generation. Uniform and and healthy seeds were selected and they were treated with various concentrations (0.1%, to 0.6%) of EMS. The EMS-treated seeds were sown in the field at CPMB (Centre for Plant Molecular Biology), Osmania University, Hyderabad. Various Quantitative traits in the M3 generation were studied. From the ANOVA results, it is evident that the difference in the mean values is highly significant due to the treatment of all the characters which indicates that there is an ample genetic variability in the genotypes. In between (IC265291 & IC265298) the genotypes in consideration, the yield parameters were shown higher by the genotype IC265298 than IC265291in M3 generation and from the data it is also evident that, as the concentration of EMS is increased, the mean values of yield parameters increased initially but further increase in the EMS concentration leads to decrease in the mean values of quantitative characters. It has been observed that the 0.2% EMS-treated seeds and 0.3% EMS-treated seeds showed the highest mean values for considered quantitative traits in M3 generation. These identified mutants may be used further in crop improvement programmes of chickpeas.